2019
DOI: 10.1038/s41598-019-53315-x
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of human limbus-derived stromal/mesenchymal stem cells for biological preservation and transportation in extreme Indian conditions for clinical use

Abstract: Human limbus-derived stromal/mesenchymal stem cells (hLMSC) can be one of the alternatives for the treatment of corneal scars. However, reliable methods of storing and transporting hLMSC remains a serious translational bottleneck. This study aimed to address these limitations by encapsulating hLMSC in alginate beads. Encapsulated hLMSC were kept in transit in a temperature-conditioned container at room temperature (RT) or stored at 4 °C for 3–5 days, which is the likely duration for transporting cells from ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Human corneal stem cells (hCSCs) were isolated and expanded as per our previously published protocol [ 20 ]. Briefly, hCSCs were isolated from collagenase digested limbal stromal tissue of human corneal rims from which central tissue had been removed.…”
Section: Methodsmentioning
confidence: 99%
“…Human corneal stem cells (hCSCs) were isolated and expanded as per our previously published protocol [ 20 ]. Briefly, hCSCs were isolated from collagenase digested limbal stromal tissue of human corneal rims from which central tissue had been removed.…”
Section: Methodsmentioning
confidence: 99%
“…To restore corneal transparency and integrity, Ad-MSCs therapy has been investigated [ 35 , 36 , 37 , 38 , 39 ]. Using clinical and animal studies, Ad-MSCs therapy has recently proven to be a promising method used in corneal reconstruction with multiple treatment approaches [ 40 , 41 , 42 , 43 ]. Moreover, it has been found that Ad-MSCs are able to provide paracrine factors in response to the wound but also able to avoid host immune rejection and transdifferentiate into multilineages [ 10 , 17 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To restore corneal transparency and integrity, Ad-MSCs therapy has been investigated [35][36][37][38][39]. Using clinical and animal studies, Ad-MSCs therapy has recently proven to be a promising method used in corneal reconstruction with multiple treatment approaches [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured on 18mm diameter coverslips in 12-well culture plates at a density of 20,000 cells/cm 2 at 37°C with 5% CO 2 in a humidi ed incubator until con uence. These cells were assessed for the expression of characteristic biomarkers of the mesenchymal stem cell (MSC) phenotype, as described previously (25). The antibody panel was composed of (a) ABCG2, Pax6, p63-α and Col-III as positive markers of the human limbal stem cell phenotype; (b) VIM, CD73, CD90, and CD105 as positive markers of the mesenchymal phenotype, and CD45 as a negative marker for mesenchymal origin.…”
Section: Assessment Of Characteristic Phenotype and Viability Of The Hlmscsmentioning
confidence: 99%
“…The hLMSCs could potentially lower the need for corneal transplantation, therefore reducing the need for donor corneas. It has also been shown that encapsulation of hLMSCs in sodium alginate, retains their phenotype and maintains the viability, while being stored or transported at varied temperatures and for prolonged durations (3-5 days) (25). This easy-to-use technology, which obviates the need for an expensive cold chain, could increase the accessibility of hLMSC-therapy, particularly in remote geographical locations, without requiring the patient to travel hundreds of miles, particularly in developing countries.…”
Section: Introductionmentioning
confidence: 99%